178k views
2 votes
Select All the correct answers

Which expressions are equivalent to this exponential expression?

A. 1/5
B.25
C.52above 5
D.5-1
E.51above 5

Select All the correct answers Which expressions are equivalent to this exponential-example-1
User AbbeGijly
by
6.2k points

2 Answers

2 votes

Answer:

B. 25

Explanation:

Plato/ Edmentum user

#platogang

User Malisokan
by
5.5k points
2 votes

Answer:

OPTION B - 25

Explanation:

We know that:


$ (a^x)^y = a^(x . y) $


$ (a^x)/(a^y) = a^(x - y) $


$ a^x . a^y = a^(x + y) $

The given problem uses these results to arrive at the answer.


$ (5^2)^(-3) = 5^(2 . (-3)) = 5^(-6) $

Now,
$ 5^(-6 + 4) = 5^(-2) $

Now,
$ (5^(-2))/(5^(-4)) = 5^(-2 -(-4)) = 5^((-2 + 4)) = 5^2  $

⇒ 5² = 25.

∴ The answer is 25. (Option B)

User Georgeok
by
5.4k points